Association of baseline diaphragm, rectus femoris and vastus intermedius muscle thickness with weaning from mechanical ventilation. (August 2021) - Er, Berrin; Simsek, Meltem; Yildirim, Mehmet; Halacli, Burcin; Ocal, Serpil; Ersoy, Ebru Ortac; Demir, Ahmet Ugur; Topeli, Arzu
Abstract: Background: To determine whether baseline diaphragm (Tdi ), rectus femoris (RF) and vastus intermedius (VI) muscle thickness (TRF and TRF + VI ) are associated with weaning success. Material and methods: Right Tdi, TRF and TRF + VI were measured by ultrasonography within 36 h of intubation and diaphragmatic excursion (DE) was evaluated at the first spontaneous breathing trial in adult critically-ill patients. Reintubation or death within 7 days after extubation was defined as weaning failure. Weaning failure and success groups were compared in terms of ultrasonographic measurements and clinical features. Results: Thirty-eight patients were assessed for weaning, 15 (39.4%) being in the weaning failure group. The median body mass index (BMI) was lower while the median clinical frailty scale (CFS), vasopressor use, duration of mechanical ventilation, intensive care and hospital mortality rate were higher in the weaning failure group, and the median TRF + VI (14.0 [12.3–26.2] vs 23.6 [21.3–27.1] mm, p = 0.03 ) and median DE (19.4 [14.6–24.0] vs 25.9 [19.3–38.5] mm, p = 0.045 ) were lower. The median Tdi was similar in two groups (1.9 [1.5–2.3] vs 2.0 [1.7–2.4] mm, p = 0.26 ). In ROC analysis, area under the curve for TRF + VI was 0.71 (95% CI: 0.51–0.90; p = 0.035 ), with 21 mm cut-off having sensitivity of 82% and specificity of 57%. Binary logistic regression analysis revealed TRF + VI < 21 mm as the only predictor of weaning failure with an odds ratio of 10.5 (95% CI: 1.1–97.8, p = 0.038 ) after adjusting for age, sex, BMI and CFS. Conclusions: TRF + VI lower than 21 mm, measured by ultrasonography within 36 h of intubation, was associated with weaning failure among critically-ill patients. Highlights: Weaning failure is associated with increased morbidity and mortality. Predicting the patients who will experience weaning failure can facilitate to direct limited resources properly. Thickness of rectus femoris and vastus intermedius lower than 21 mm measured by ultrasound predicted weaning failure better than other variables.